ON THE NATURE AND LICENSING CONDITIONS OF N-PHRASES IN PORTUGUESE - Peres, João Andrade (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
The present paper focuses on the syntactic and semantic nature of the expressions identified in the literature as n-words (preferably, n-phrases), and on their licensing conditions. Concerning their status, arguments will be given in favor of Ladusaw’s 1992 thesis that these are existential (and non-specific, it is claimed) indefinites. In a brief excursus, it will be shown that other constructs engage in the process known as “negative concord”. In the final part, an attempt will be made to offer a systematic picture of the intra– and cross-sentential licensing conditions of classical n-phrases. In this regard, the paramount importance of contextual decreasing monotonicity becomes apparent